(untitled) (Journal of Fiber Bioengineering and Informatics, 2023)
This paper reports a study of 13 Japanese women who wore two types of pantyhose that were rated as providing an “almost-perfect pressure sensation” and three types of shoes. The root mean square of the electromyogram for eight muscles in the right leg was calculated. RMS has divided four group muscles: into each muscle around the knee, around the knee, on the ventral side, and on the dorsal side, and investigated how it changes between bare feet, pantyhose, and shoes. Each pantyhose is designed to stretch the legs well and follow the walking motion easily, but pantyhose B is double woven from the abdomen to the backside so as to connect to the back side while lifting the subcutaneous fat of the abdomen. Even if the pantyhose is made to apply almost the same pressure to the ankles, changing the design of the panty part can activate or suppress abdominal muscle activity.